Pattern-based development of digital platforms - Marvin Drewel; Leon Özcan; Christian Koldewey; Jürgen Gausemeier (Creativity and Innovation Management, 2021)
Digital platforms have been reshaping the structure of whole industries. Whereas previous developments mainly have taken place within the business-to-consumer (B2C) or consumer-to-consumer (C2C) market, the business-to-business (B2B) market is at the edge of the so-called platform economy. Leading companies step out of their core business and develop their own platforms. The paper at hand presents a methodology to master the challenges of developing digital platforms by using patterns, which represent proven principles of already established platforms. The methodology is based on a holistic pattern catalogue that can be used independently from the task at hand. We show in detail how we derived a catalogue with 37 platform patterns and how the catalogue can be applied to the development of digital platforms. The corresponding methodology contains three phases. Within the first phase, a specific platform idea is being developed. The second phase addresses the collaboration of an platform concept. Finally, a specific digital platform concept is worked out.
Keywords: 330; B2B platforms; digital platform; manufacturing industry; multisided markets; platform economy; platform markets